Performance Evaluation of NAS Parallel and High-Performance Conjugate Gradient Benchmarks in Mahameru - Wirahman, Taufiq; Latifah, Arnida L; Muttaqien, Furqon Hensan; Swardiana, I Wayan Aditya; Arisal, Andria; Iryanto, Syam Budi; Sadikin, Rifki (JOIN (Jurnal Online Informatika), 2025)
High-Performance Computing (HPC) plays a crucial role in accelerating scientific advancement across numerous fields of research and in effectively implementing various complex scientific applications. Mahameru is one of the largest national HPC systems in Indonesia and has been utilized by many sectors. However, it has not undergone proper benchmarking evaluation, which is vital for identifying issues related to hardware and software configurations and confirming system reliability. Therefore, this study aims to evaluate the performance, efficiency, and capabilities of Mahameru. We present a benchmarking system on Mahameru utilizing two benchmark suites: the NAS Parallel Benchmarks (NPB) and the high-performance conjugate gradient (HPCG) benchmark. Our results indicate that the NPB exhibits a lower speedup in Message Passing Interface (MPI) compared to OpenMP, which can be attributed to the communication overhead and the nature of the computational tasks. Additionally, the HPCG benchmark demonstrates that Mahameru performance can compete with the lower tiers of the Top 500 supercomputers. When operating at full capacity, Mahameru can achieve approximately 2.5% of its theoretical peak performance. While the system generally performs reliably with parallel algorithms, it may not fully leverage hyperthreading with certain algorithms. This benchmark result can serve as a basis for decision-making regarding potential upgrades or changes to a system.